The Valuation of Options on Futures Contracts - RAMASWAMY, KRISHNA; SUNDARESAN, SURESH M. (Journal of Finance, 1985)
ABSTRACT Rational restrictions are derived for the values of American options on futures contracts. For these options, the optimal policy, in general, involves premature exercise. A model is developed for valuing options on futures contracts in a constant interest rate setting. Despite the fact that premature exercise may be optimal, the value of this American feature appears to be small and a European formula due to Black serves as a useful approximation. Finally, a model is developed to value these options in a world with stochastic interest rates. It is shown that the pricing errors caused by ignoring the location of the interest rate (relative to its long‐run mean) range from −5% to 7%, when the current rate is ±200 basis points from its long‐run value. The role of interest rate expectations is, therefore, crucial to the valuation. Optimal exercise policies are found from numerical methods for both models.